The impact of retirement on inpatient healthcare utilization in Guangzhou, China: a regression discontinuity analysis of 189,031 health insurance claims - Zhao, Xintong; Liu, Yuehua; Zhang, Xin; Bärnighausen, Till; Chen, Simiao (BMC geriatrics, 2022)
Previous studies suggest that retirement, a major life event, affects overall healthcare utilization. We examine, the effects of retirement on inpatient healthcare utilization, including effect heterogeneity by gender, disease category, and type of health service.